Evaluating and comparing the clinical characteristics between adult-onset and childhood-onset atopic dermatitis in an Asian clinical cohort - Aponso, Shashendra (2023)
Atopic dermatitis (AD) is one of the most prevalent chronic inflammatory skin conditions. We aimed to describe the clinical features of adult-onset and childhood-onset AD in a multi-ethnic Asian population.